Effects of emotional arousal on multiple memory systems: Evidence from declarative and procedural learning - Steidl, Stephan (Cold Spring Harbor Laboratory Press, 2006)
Extensive evidence documents emotional modulation of hippocampus-dependent declarative memory in humans. However, little is known about the emotional modulation of striatum-dependent procedural memory. To address how emotional arousal influences declarative and procedural memory, the current study utilized (1) a picture recognition and (2) a weather prediction (WP) task (a probabilistic classification learning task), which have been shown to rely on hippocampal- and striatum-based memory systems, respectively. Observers viewed arousing or neutral pictures after (Experiment 1) or during (Experiment 2) WP training trials. A 1-wk delayed picture recognition memory test revealed enhanced declarative memory for arousing compared with neutral pictures. Arousal during encoding impaired initial WP acquisition but did not influence retention when tested after a 1-wk delay. Data from a subsequent 3-mo delayed test, however, suggested that arousal during acquisition may enhance remote WP retention. These results suggest a potential dissociation between how readily emotional arousal influences hippocampus-dependent and striatum-dependent memory systems in humans.